Malaysian journal of mathematical sciences
The Malaysian Journal of Mathematical Sciences publishes original research papers and review articles on and related to mathematical sciences, covering topics in the areas of but not limited to theoretical and applied mathematics, statistics, industrial mathematics, biomathematics, mathematics education and history of mathematics. MJMS is indexed and abstracted in SCOPUS, Islamic World Science Citation Center (ISC) and Zentralblatt MATH databases.